Early Child Marriage: Customary Law, Support System, and Unwed Pregnancy in Gorontalo - Wantu, Sastro Mustapa; Abdullah, Irwan; Tamu, Yowan; Sari, Intan Permata (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
The rate of underage marriage in Gorontalo is very high, even though religion, customs and state laws prohibit it. The results of the direct interviews conducted and the observations made indicate that poverty, low levels of education and matchmaking myths may have caused this increase. Furthermore, the increasingly high level of promiscuity and weakened socio-cultural ties have led to an increase in the number of extramarital pregnancies, and forced marriage is unavoidable to maintain the dignity of the community. It was discovered that most married couples do not wed legally until they have problems in their marriage and seek a divorce. Moreover, women must also be responsible for their life choices because this paper shows that poor service practices have caused underage women to be objectified by physical, social and symbolic violence. The unavailability of a support system from the government and society makes a partner rely on the kindness of his or her parents. Therefore, it was suggested that government intervention, in the form of prevention and support systems for underage married women, must be integrated with the role of the community and religious leaders.